Digital Literacy Competencies: A Study of Distance Learners of Higher Education Regulatory Authority Khyber Pakhtunkhwa - Razzaq Ahmad, Sheikh Tariq Mehmood,Safeer Ija (PJDOL, 2023)
With the use of technology, students can store, share, and record what they learned in a given session or day of remote learning. This study aimed to assess distance learners’ abilities in digital literacy by examining their attitudes, concepts, and methods. The quantitative descriptive survey research method was used. For this purpose, 95 distance learners were selected from the different private colleges in district Swabi that were affiliated with Higher